Reconstrucción de un monetario: la colección de moneda indiana de la Real Academia de la Historia a través de la documentación del Archivo Gabinete Numario - Martín Escudero, Fátima (Revista General de Información y Documentación, 2009)
Since its foundation, the Royal Academy of History has formed a monetary collection as a primary source which helps to elaborate a history of Spain. The collection was formed through purchases and donations; at the same time, the Numismatic Archive was created, where all these facts and other numismatic news are hold. Thanks to the study, organization and publication of the Archive, as well as the coin collections, it is possible to recreate its process of construction. The purpose of this paper is to analyze the documentation related to Spanish colonial coins, focusing on the origin and development of this section of the collection and locating documentated items.